Calpain Activity and Toll-Like Receptor 4 Expression in Platelet Regulate Haemostatic Situation in Patients Undergoing Cardiac Surgery and Coagulation in Mice - Tsai, Jui-Chi; Lin, Yi-Wen; Huang, Chun-Yao; Lin, Feng-Yen; Tsai, Chien-Sung (Mediators of Inflammation, 2014)
Human platelets express Toll-like receptors (TLR) 4. However, the mechanism by which TLR4 directly affects platelet aggregation and blood coagulation remains to be explored. Therefore, in this study, we evaluated the platelet TLR4 expression in patients who underwent CABG surgery; we explored the correlation between platelet TLR4 expression and the early outcomes in hospital of patients. Additionally, C57BL/6 and C57BL/6-TlrLPS−/− mice were used to explore the roles of platelet TLR4 in coagulation by platelet aggregometry and rotation thromboelastometry. In conclusion, our results highlight the important roles of TLR4 in blood coagulation and platelet function. Of clinical relevance, we also explored novel roles for platelet TLR4 that are associated with early outcomes in cardiac surgery.